Improving Equity, Diversity, and Inclusion in Plastic, Reconstructive, and Aesthetic Surgery in Canada: A Call to Action. Issue 2 (May 2022) - Snell, Laura; Valiquette, Chantal R.; Avery, Emma; Moltaji, Syena; Forrest, Christopher R.
The global COVID-19 pandemic has brought to light the significant inequities in the delivery of healthcare, vaccine inequity, and differential access to life-saving treatments, which have disproportionately impacted marginalized and racialized populations. In this article, we acknowledge and recognize the centuries-old legacies perpetuating inequity, injustice, and oppression, we discuss the principles of Equity, Diversity, and Inclusion (EDI) and we call our Canadian plastic surgery colleagues and trainees to action. We propose a plan for (1) Education, (2) Mitigating Disparities in the Clinical Setting, and (3) Policy, Societies, and Leadership Education.